Prevalence and associated factors of infantile colic in infants of mothers in medical residency program - Muzal Kadim; Wira Febrisandi Irsan; Tjhin Wiguna; Dina Muktiarti; Sulaiman Yusuf; Ade Rachmat Yudianto; Yusri Dianne Jurnalis; Yudith Setiati Ermaya; Wahyu Damayanti; Andy Darma; Christy Venada (Paediatrica Indonesiana, 2026)
Background  Infantile colic, defined according to the Rome IV criteria as excessive crying in otherwise healthy infants without signs of illness or failure to thrive, could be linked to inadequate mother–infant bonding. The risk of infantile colic is increased in mothers with depression and insufficient family support. Infantile colic could lead to recurrent emergency department admissions, unnecessary treatments, and child abuse. Mothers in medical residency programs who often face long working hours, reduced bonding time with their infants, burnout, and depression, may be at an increased risk of having infants with colic. However, data on the prevalence and associated factors of infantile colic in infants of mothers in this specific population are lacking. Objective To determine the prevalence of infantile colic and its associated factors among infants of mothers participating in medical residency programs. Methods We conducted a cross-sectional study involving 67 infants of mothers in medical residency programs across seven centers in Java and Sumatra. We used the Indonesian-translated Parent Report Questionnaire for Children Aged 0-3 Years from the Rome Foundation to obtain information on infantile colic based on Rome IV criteria and the Indonesian version of the Mother-Infant Bonding Scale Questionnaire to assess the risk level of mother-infant bonding problems. An online questionnaire was distributed to subjects’ mothers via WhatsApp© application. Results  Of 67 subjects, 18 (26.8%) experienced infantile colic. High risk of mother–infant bonding problems, as indicated by elevated Mother-Infant Bonding Scale-Indonesian version (MIBS-I) scores, were significantly associated with infantile colic (OR 2.922; 95%CI 1.07 to 4.87; P=0.046). The type of nutrition, whether breast milk or a combination of formula and breast milk, did not significantly differ between infants with and without colic (OR 1.333; 95%CI 0.451 to 3.940; P=0.602). Conclusion Elevated MIBS-I scores, reflecting impaired mother–infant bonding, are ssociated with an increased risk of infantile colic in infants born to mothers in medical residency training programs.